Selection of mutant Chinese hamster ovary cells altered glycoproteins by means of tritiated fucose suicide. - Hirschberg, C B (1981)
Mutant Chinese hamster ovary cells altered in glycoproteins have been isolated by selecting for ability to survive exposure to [6-3H]fucose. Mutagenized wild-type cells were permitted to incorporate [3H]fucose to approximately 1 cpm of trichloroacetic acid-insoluble radioactivity per cell and then frozen for several days to accumulate radiation damage. The overall viability of the population was reduced by 5- to 50-fold. Four consecutive selection cycles were carried out. The surviving cells were screened by replica plating-fluorography for clones showing decreased incorporation of fucose into trichloroacetic acid-insoluble macromolecules. Considerable enrichment for cells deficient in fucose uptake or incorporation into proteins (or both) was found in populations surviving the later selection cycles. Two mutant clones isolated after the fourth selection cycle had the same doubling time as the wild type, but contained only 30 to 40% as much fucose bound to proteins as the wild type. Sialic acid contents of the mutants and the wild type were similar. The mutants differed quantitatively and qualitatively from the wild type and from each other with respect to total glycoprotein profiles as visualized by sodium dodecyl sulfate gel electrophoresis. Differences were also found in resistances to cytotoxicity of lectins such as concanavalin A and wheat germ agglutinin.